Effect of Different Nutrient Concentrations on the Growth and Yield of Curly Lettuce (Lactuca sativa L.) in Two Hydroponic System - Febriani, Annisa Gita; Aisyah, Aisyah; Edi Minadji Pribadi; Bagas Elang Samudra (Journal of Smart Agriculture and Environmental Technology, 2025)
Lettuce (Lactuca sativa L.) is a widely consumed vegetable known for its nutritional benefits and economic potential. This study investigated the effects of two hydroponic systems Nutrient Film Technique (NFT) and Deep Flow Technique (DFT) and varyied nutrient concentrations on the growth and production of curly lettuce, conducted from March to June 2024 at the Smart Farming Zone of UG Technopark, the research utilized a Randomized Complete Block Design (RCBD) with two nested factors. The first factor comprised two hydroponic systems (H1: NFT and H2: DFT), while the second factor involved four nutrient combinations: AB Mix 0 ml + Liquid Organic Fertilizer (LOF) 10 ml (P1), AB Mix 5 ml + LOF 15 ml (P2), AB Mix 10 ml + LOF 20 ml (P3), and AB Mix 20 ml + LOF 25 ml (P4). Key growth parameters measured included plant height, number of leaves, leaf  length, leaf width, stem diameter, root length, total fresh weight, fresh weight of roots, and total dry weight. Results indicated that the DFT hydroponic system with a nutrient concentration of AB Mix 20 ml + LOF 25 ml significantly enhanced plant height, number of leaves, root length, fresh weight of the crown, and dry weight. Additionally, the DFT system at AB Mix 10 ml + LOF 20 ml improved leaf length, leaf width, stem diameter, and fresh weight of curly lettuce. These findings underscore the potential of optimizing hydroponic systems and nutrient formulations for enhanced lettuce production.